New lignans and diterpenoid glycosides from the fruits of Xanthium italicum Moretti. Issue 6 (3rd June 2022) - Li, Yu-Tong; Fu, Jiang; Wang, Hai-Qiang; Li, Yong; Liu, Yun-Bao; Ma, Shuang-Gang; Qu, Jing; Yu, Shi-Shan
Abstract: A pair of new lignans [(+)- 1 and (-)- 1 ] and three new compounds (2-4 ), together with a known compound 5, were isolated from the fruits of Xanthium italicum Moretti. The structures of these compounds were determined on the basis of spectroscopic analysis, particularly HR-ESI-MS and 1 D and 2 D NMR. Compounds 2 and 3 showed antinociceptive effects in an acetic acid-induced writhing test in mice with the writhe inhibition rates of 80.50% and 67.89% at the dose of 20 mg/kg, respectively. Abstract : UF0001